2010
DOI: 10.2174/156720510792231775
|View full text |Cite
|
Sign up to set email alerts
|

Is Elevated Norepinephrine an Etiological Factor in Some Cases of Alzheimers Disease?

Abstract: Loss of norepinephrine (NE) releasing neurons, in the locus coeruleus of the brainstem, is well documented to occur in Alzheimer's disease (AD). However, this process does not necessarily result in decreased release of NE, since compensatory mechanisms may produce increased release of this neurotransmitter. Independent of potential loss of locus coeruleus cells, brain NE levels may be elevated in some persons with AD, both before and during disease progression. Here I examine evidence that elevated, endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 131 publications
0
19
0
Order By: Relevance
“…Molecular modeling showed that despite these changes, all amphipathic helices that are required for Apo E-lipid interactions are conserved [7]. Although direct measurements of vervet (or related species) apo E to amyloid have not been done, in cynomolgus monkeys (Macaca fascicularis), apo E was co-localized to plaques with amyloid deposits [11] suggesting a functional interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular modeling showed that despite these changes, all amphipathic helices that are required for Apo E-lipid interactions are conserved [7]. Although direct measurements of vervet (or related species) apo E to amyloid have not been done, in cynomolgus monkeys (Macaca fascicularis), apo E was co-localized to plaques with amyloid deposits [11] suggesting a functional interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the levels of the rate limiting enzyme TH were found to be increased in the remaining neurons in the LC of AD brains [47], as well as increased dendritic sprouting in the LC, and increased axonal projections to the hippocampus [48]. Indeed it has been suggested that elevated NA levels may contribute to AD pathogenesis [11]. While the current study is underpowered to allow strong conclusions to be drawn, our data suggests that in aged vervet temporal cortex, at least some animals show lower NA levels than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ(1-42) induces internalization and degradation of β2 adrenergic receptors in prefrontal cortical neurons (Wang et al, 2011). Furthermore, it has been hypothesized that elevated norepinephrine may be an etiological factor in some cases of AD (Fitzgerald, 2010) and Bullido et al (2004) described polymorphism in genes involved in adrenergic signaling associated with AD. Recently, Femminella et al (2013) have written an article whose title is very suggestive: “β-adrenergic receptors and G protein-coupled receptor kinase-2 in Alzheimer’s disease: a new paradigm for prognosis and therapy?,” as suggestive is part of the summary of the Yu et al (2010) review: “ In the recent years, several unexpected longitudinal and cross-sectional epidemiological studies reveal that beta-blocker treatment reduces the prevalence of AD in patients suffering from hypertension.…”
Section: Lessons From Adrenergic-receptor-based Interventionsmentioning
confidence: 99%
“…These findings confirm the presumption that initial loss of noradrenergic neurons from the LC is compensated by the increased activity of the surviving neurons (American Psychiatric Association, 1994; Hoogendijk et al, 1999; Szot et al, 2006). Several compensatory mechanisms have been described (Counts and Mufson, 2010: Fitzgerald, 2010; Szot et al, 2006; Weinshenker, 2008), including stimulation of NA synthesis due to the increased expression of TH (Szot et al, 2006), decreased clearance of NA from the presynaptic terminals (Raskind et al, 1999), impaired NA turnover (Counts and Mufson, 2010; Fitzgerald, 2010; Weinshenker, 2008), and increased sprouting of the surviving noradrenergic neurons originating from LC (Szot et al, 2006). The determination of NA and its metabolite 3-methoxy-4-hydroxyphenylglycol (MHPG) revealed a high MHPG/NA ratio in frontal cortex and LC in AD (Hoogendijk et al, 1999), suggesting that increase in NA metabolism in remaining noradrenergic neurons could be also a potential compensatory mechanism for the loss of noradrenergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increases in cerebrospinal fluid (CSF) NA levels (Elrod et al, 1997; Raskind et al, 1999) in AD support the hypothesis that increased noradrenergic activity represents a compensatory mechanism for both cholinergic and noradrenergic deficits (Giubilei et al, 2004; Herrmann et al, 2004). There are several mechanisms providing evidence for the role of NA in AD as not merely a risk factor but as an actual etiological factor (Counts and Mufson, 2010; Fitzgerald, 2010; Weinshenker, 2008). Neuronal plasticity resulting in hyperinnervation of the forebrain regions and noradrenergic sprouting to reinnervate brain regions marked by loss of cholinergic neurons might be mechanisms that account for this compensation (McMillan et al, 2011; Szot et al, 2006).…”
Section: Introductionmentioning
confidence: 99%